Adaptações em forno de microondas doméstico para utilização em laboratório - Pecoraro, Édison [UNESP]; Davolos, Marian Rosaly [UNESP]; Jafelicci Júnior, Miguel [UNESP] (Sociedade Brasileira de Química, 1997)
Domestic microwave oven was modified for laboratory applications. Electronic system was made for controlling magnetron irradiation time. Exhaustion and air circulation systems were installed to clean the internal oven atmosphere during operation. The cavity walls were coated with aluminized thermal paint to avoid chemical corrosion. These modifications allowed the usage of the oven for drying and processes using reflux.
Microwave oven modifications for laboratory applications
Keywords: microwave oven